Control del tórsalo (Dermatobia hominis, L. Jr.) con insecticidas orgánicos fosforados, de acción sistémica - Graham, O. H.; Kraemer, P; Osorio, A. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Several organic-phosphorus insecticides that had shown promise for the control of the North American cattle grub Hypoderma bovis (L) and H. lineatum (De Vill.) by systemic action, were tested against the torsalo, Dermatobia hominis (L., Jr.), in Nicaragua. Oral doses of American Cyanamid 12.880, Dowco 105, Dowco 109, and Dipterex were more effective than oral doses of Bayer 21/199 and Dow ET-57. American Cyanamid 12880 was also effective when administered by injection and as a spray. Although the better systemic insecticides appear to kill almost all the torsalo present at the time of treatment, their large-scale use will probably be limited by such factors as cost, failure to prevent reinfestation, and the appearance of residues in the milk of cows